2021
DOI: 10.3390/w13131769
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint and Virtual Water Trade of Maize in the Province of Buenos Aires, Argentina

Abstract: Agriculture is the largest fresh water consuming sector, and maize is the most produced and consumed crop worldwide. The water footprint (WF) methodology quantifies and evaluates the water volumes consumed and polluted by a given crop, as well as its impacts. In this work, we quantified for the first time the green WF (soil water from precipitation that is evapotranspired) and the green virtual water exports of maize from Buenos Aires province, Argentina, during 2016–2017, due to the relevance of this region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Work by Kashifi et al (2022) has shown that for Saudi Arabia, importing certain crops (maize, wheat and rice) could significantly reduce the local water footprint, energy costs and greenhouse gas emissions. Indeed, virtual water trade in maize from Argentina has helped other water scarce nations meet their water security and water-dependent food security needs (Arrien et al, 2021). Human labor and social wellbeing are also a significant component of these trade networks.…”
Section: Unveiling the Globalization Of Nexus Resource Systemsmentioning
confidence: 99%
“…Work by Kashifi et al (2022) has shown that for Saudi Arabia, importing certain crops (maize, wheat and rice) could significantly reduce the local water footprint, energy costs and greenhouse gas emissions. Indeed, virtual water trade in maize from Argentina has helped other water scarce nations meet their water security and water-dependent food security needs (Arrien et al, 2021). Human labor and social wellbeing are also a significant component of these trade networks.…”
Section: Unveiling the Globalization Of Nexus Resource Systemsmentioning
confidence: 99%
“…In recent years, research conducted in Argentina has evaluated the water-food-trade nexus through virtual water trade [18,19]. Virtual water refers to the volume of fresh water used in the production of a commodity or a service, and which is then traded [20].…”
Section: Introductionmentioning
confidence: 99%
“…For their part, Dumont et al [19] and De Migue et al [20] conducted their studies at the basin level in Spain. At the municipal level, the studies by Manzardo et al [21] developed a method to take into account the water footprint at the urban level to support water management in Vicenza, northern Italy, while Arrien et al [22] adopted the municipal scale to quantify the water footprint of corn in the Province of Buenos Aires, Argentina. The aforementioned studies are examples of how the water footprint approach is a valuable tool to explore water use and determine its sustainability, mainly in the agriculture sector [23], at different scales, and how this tool helps in the management of sustainable water resources in the medium and long term [24].…”
Section: Introductionmentioning
confidence: 99%